Veiling and Lipstick in the City: Being Female, Young and Muslim in Urban Mindanao - Taqueban, Efenita Mae (Philippine Social Sciences Review; PSSR Vol. 70 No. 2 2018, Ed. Ariel C. Lopez, 2021)
Framing young female Muslim students as figures of modernity “who loom larger than life because they alternately express and challenge conventional understandings of social types” (Baker, Harms & Lindquist, 2014), this paper reflects on the young women’s everyday beauty practices as a way to apprehend their notions of identity and beauty. Looking at the seemingly mundane but increasingly ubiquitous practice of cosmetics use, what does this tell us about the young women’s modern condition? What emerge are contested figures of young Muslim women, often characterized by tropes of subservience and obedience, as active explorers of new trends and femininities, using new products to form new identities and reframe traditional notions of self and beauty. They straddle between assertions of individuality and belonging to a community; proud keepers of tradition at the same time espousing modern ethos.
Keywords: Beauty, cosmetics, veil, modernity, Maranao students